Palynofacies and Source Rocks Evaluation for Selected Samples of Subba Oil Field, Southern Iraq - Chafeet, Hussein A.; Dahham, Nawfal A.; Handhal, Amna M. (Iraqi Journal of Science, 2020)
This study includes a palynological and organic geochemical evaluation of Nahr Umr, Zubair, and Yamama Formations in the Subba field, Southern Iraq, represented by three wells (Su-14, Su-9 and Su-8). The determination of quantity organic matter showed that the rocks of Nahr Umr Formation had a total organic carbon of 4.76%, indicating very good production of hydrocarbons where type (II) kerogen was dominant, but the rocks were thermally immature. Zubair Formation had a total organic carbon of 1.91% to 2.26%, indicating good to very good production of hydrocarbons where kerogen of types (I) and (II/III) were dominant, with low thermal maturity. Yamama Formation showed a total organic carbon of 1.68%, revealing good production of hydrocarbons where type (I) kerogen was dominant, with low thermal maturity. Facies analysis of Nahr Umr, Zubair and Yamama Formations demonstrated the presence of two facies, namely the distal dysoxic-Oxic shelf and the distal suboxic-Anoxic basin. It is clear that the environment of rock deposition is a marine environment, which is far from the coast.